Effect of different concentrations of Taurine on certain physico -morphological attributes during cryopreservation of Gir bull semen - Chikhaliya, P S; Ahlawat , AR; Talekar , SH; Chaudhary , JK (Indian Journal of Dairy Science, 2022)
The study was carried out on four Gir bull (4-6 years) located at Cattle Breeding Farm J.A.U. Junagadh for a period of 6 weeks. Semen was collected using artificial vagina method once weekly for six weeks from each of the bulls A Total 8 semen sample from four healthy Gir breeding bulls were collected at weekly interval for two weeks period using of artificial vagina method for evaluation of semen biochemical attributes at various stages of cryopreservation of Gir bull semen. The semen was evaluated for physical characteristics at per-freeze and post-thaw stages of cryopreservation using different Taurine concentrations viz. 25 mM Taurine, 50 mM Taurine, 75 mM Taurine and control was kept.At pre-freeze stages of cryopreservation, 50 mM Taurine group had value of 70.20 ± 1.22, 69.87 ± 3.09, percent for individual motility and sperm viability, respectively, value were significantly (P<0.05) higher as compared to that of the 25 mM Taurine, 75 mM Taurine and control groups. Mean per cent sperm abnormality was 15.37 ± 0.89 in 50mM Taurine group at pre-freeze stages of cryopreservation, which were significantly (P<0.05) lower as compared to that of the other groups.At post-thaw stages of cryopreservation, 50 mM Taurine group had value of 62.70 ± 0.42, 65.66 ± 0.58, percent for individual motility andÂ sperm viability respectively, value were significantly (P<0.05) higher as compared to that of the 25 mM Taurine, 75 mM Taurine and control groups. Mean per cent sperm abnormality was 20.29 ± 0.73 in 50mM Taurine group at post-thaw stages of cryopreservation, which were significantly (P<0.05) lower as compared to that of the other groups.All of above physico-morphological were better in 50 mM Taurine group at pre-freeze and post-thaw stages of cryopreservation.